A device for the fabrication of multifunctional particles from microbubble suspensions - GÜNDÜZ, OĞUZHAN (ELSEVIER, 2012)
A novel V-junction microfluidic (VJM) device has been used to generate several types of particles from the break-up of bubbles. The flow rates of selected solutions and the gas pressure were adjusted in order to successfully generate monodisperse polymer coated microbubbles, which serve as a platform for particle generation. Uniform particles in both the nano and micro size ranges with different shapes were spontaneously generated from bubbles and have the potential to be used in several advanced technological applications. (C) 2012 Elsevier BM. All rights reserved.
Keywords: Microfluidic device; Microbubbles; Particles; GENERATION; RELEASE; DRUGS; CHIP